2018
DOI: 10.1111/ajt.14434
|View full text |Cite
|
Sign up to set email alerts
|

Human immunology studies using organ donors: Impact of clinical variations on immune parameters in tissues and circulation

Abstract: Organ donors are sources of physiologically healthy organs and tissues for life-saving transplantation, and have been recently used for human immunology studies which are typically confined to the sampling of peripheral blood. Donors comprise a diverse population with different causes of death and clinical outcomes during hospitalization, and the effects of such variations on immune parameters in blood and tissues are not known. We present here a coordinate analysis of innate and adaptive immune components in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 45 publications
3
81
1
1
Order By: Relevance
“…We note that the purpose of our study is to demonstrate how omics data can be used to calibrate a QSP model, rather than to qualify a model for application in drug development. Figure 3 shows the constraints on state variables in the minimal CIC model based on data from "Immune Landscape of Cancer" (Figure 1a,b), high-throughput flow cytometry of human donor tissues, [13][14][15] T-cell repertoire sequencing, 16 and the established literature of basic cellular composition of the immune system. State variables describing cell populations in most QSP models in IOincluding the minimal model presented here-are expressed as absolute cell numbers rather than relative amounts.…”
Section: Minimal Model Calibration Using Omics Datamentioning
confidence: 99%
See 1 more Smart Citation
“…We note that the purpose of our study is to demonstrate how omics data can be used to calibrate a QSP model, rather than to qualify a model for application in drug development. Figure 3 shows the constraints on state variables in the minimal CIC model based on data from "Immune Landscape of Cancer" (Figure 1a,b), high-throughput flow cytometry of human donor tissues, [13][14][15] T-cell repertoire sequencing, 16 and the established literature of basic cellular composition of the immune system. State variables describing cell populations in most QSP models in IOincluding the minimal model presented here-are expressed as absolute cell numbers rather than relative amounts.…”
Section: Minimal Model Calibration Using Omics Datamentioning
confidence: 99%
“…In a series of recent studies, Farber's group applied high-throughput flow cytometry to organ donor tissues to quantitatively describe the state of the immune system in healthy individuals. [13][14][15] These unique data provide insight into relative distributions of multiple T-cell types and dendritic cells among different tissues, including lymph nodes. Thome et al 13 studied tissues from 56 donors and determined the distribution of CD4 and CD8 T-cells in peripheral blood, spleen, inguinal lymph node (draining the peripheral skin and muscle), lung-draining lymph node, lungs, mesenteric lymph node (draining the intestines), small intestine (jejunum and ileum), and colon.…”
Section: The Omics Data Coverage Of Cancer Immunity Cyclementioning
confidence: 99%
“…These findings suggest that localization of T cells in tissues likely involves structural changes in the cell that facilitate interactions with tissue matrix. 9 We compared the single-cell distribution of average expression of tissue signature genes in the blood and three tissues ( Fig. 3d).…”
Section: A Universal Gene Signature Distinguishes Tissue T Cells Frommentioning
confidence: 99%
“…In humans, most of our knowledge of T cell activation and function derives from the sampling of peripheral blood. Recent studies in human tissues have revealed that the majority of human T cells are localized in lymphoid mucosal and barrier tissues 8 and that T cell subset composition is a function of the specific tissue site 9,10 . Human TRM cells can be defined based on their phenotypic homology to mouse TRM and are distinguished from circulating T cells in blood and tissues by a core transcriptional and protein signature [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation